ANALISIS DAMPAK CUSTOMER SERVICE TERHADAP LOYALITAS DI SWAMITRA ASMINDO SURAKARTA - Suroyo Suroyo; Parlin Sinaga; Aprianto Miduk Pandapotan Saragih (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The most important factor in determining a company's success and quality is its ability to serve its customers. After analysis, if there are any signs of customer dissatisfaction, the attribute causing the dissatisfaction should be identified and corrective action taken or resolved. Analyzing the level of service that has been provided, Swamitra Asmindo Surakarta has been paying attention to Customer Satisfaction. This survey uses survey design, specifically the primary data collection method for asking each respondent. This survey was conducted by distributing surveys to clients using Swamitra Asmindo Surakarta's deposit service. The results of the tests performed can show that the quality of service has a significant impact on aspects such as concreteness, reliability, responsiveness, security and empathy.. on customer satisfaction at Swamitra Asmindo Surakarta. So, the first hypothesis in this study is provenThe results of the calculation of the value of t (partial) to the value of F (together) Swamitra Asmindo Surakarta has a significant impact on quality of service and customer satisfaction. Five measures, including tangible, reliable, responsive, safe and empathic, will be further considered and qualitatively improved.